2010
DOI: 10.1177/097168581001600103
|View full text |Cite
|
Sign up to set email alerts
|

Education and Employment Issues for Indigenous Australians in Remote Regions

Abstract: Despite government policy and initiatives for remote areas, indigenous people are amongst the most disadvantaged and do exhibit higher levels of unemployment in the Australian community. A number of commentators have suggested that better educational opportunities for this minority group will considerably improve their socio-economic status and employment opportunities. This myth is exposed in this article, which reports evidence from an educational–vocational programme for Yolngu who are the indigenous people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…Contrary to predictions, non-mining SLAs did not lose populations to mining SLAs. The small Indigenous populations in mining SLAs confirm their displacement , despite efforts by some mining companies to accommodate them (Pearson and Daff, 2010). With respect to industry structure, the results showed a bigger and growing construction sector, a smaller and contracting social services sector and a smaller but stable primary sector for mining SLAs compared to non-mining SLAs.…”
Section: Discussionmentioning
confidence: 84%
“…Contrary to predictions, non-mining SLAs did not lose populations to mining SLAs. The small Indigenous populations in mining SLAs confirm their displacement , despite efforts by some mining companies to accommodate them (Pearson and Daff, 2010). With respect to industry structure, the results showed a bigger and growing construction sector, a smaller and contracting social services sector and a smaller but stable primary sector for mining SLAs compared to non-mining SLAs.…”
Section: Discussionmentioning
confidence: 84%
“…Jackson and Barber (2015) also find that Aboriginal Australians may be excluded from mining-related growth due to rapid population growth coupled with low educational outcomes. Other research has shown the insufficiency of only providing training for Indigenous populations (Pearson and Daff, 2010;Jackson and Barber, 2015).…”
Section: Background and Literaturementioning
confidence: 99%
“…Australians have a long history of suffering discrimination, including in the formal education system (Reynolds 1989;Pearson 1994;Orr 1999;Wenitong et al 2007;Gray and Beresford 2008;Pearson and Daff 2010). After being granted citizenship by the government in 1967, indigenous Australians participated in multiple government education integration programs (Biermann 2008;Orr 1999).…”
Section: Contemporary Indigenous Education Policies Differ Across Ocementioning
confidence: 99%